Identifikasi Tingkat Pencemaran Air Permukaan di Sub Daerah Aliran Sungai (DAS) Way Kandis Hulu - Diano Hadi Putra; Gisnia Amaliyah; Siti Kholofah; Didik Kuswadi (Jurnal Ilmiah Teknik Pertanian - TekTan, 2015)
Generally, pollution in the waters is indicated with the presence of oxygen in the water or dissolved oxygen condition. To determine status of oxygen in the water as water pollution level  necessary to measure the COD (Chemical Oxygen Demand), TSS (Total Suspended Solid), TDS (Total Dissolve Solid) and turbidity (turbidity) as parameters of river water pollution. The purpose of this study is (1) to analyze the water quality of the sub watershed upstream Way Kandis, (2) make a map of the level of contamination of surface water in Sub Watershed (DAS) upstream Way Kandis. Stages of research include (i) gathering information and data, (ii) analysis of land use in sub watershed upstream Way Kandis, (iii) the analysis of water quality of upstream Way Kandis (iv) making maps contamination levels upstream Way Kandis, (v) the analysis of the level of River pollution Way Kandis. The results of this research, namely: (1) upstream Way Kandis watershed covering an area of 4603.76 hectares which includes the city of Bandar Lampung Territory and South Lampung regency and spread over four districts, namely Kemiling, Rajabasa, Natar and Jatiagung, (2) Usage land upstream Kandis Way watershed includes residential area of 3285.71 ha (71.37%), plantations covering an area of 429.52 ha (9.33%), a mixture of agricultural land area of 627.19 ha (13.62%), and poor land identified as the source map cloud-covered area of 118.98 ha (2.59%), (3) The level of water pollution in the upstream Way Kandis watershed divided into five zones, namely zones not polluted, slightly polluted zone, the critical zone polluted, heavily polluted and heavily polluted, (4) the highest COD pollution level in the class Very polluted covering an area of 2250.98 hectares or 48.79% of the total upstream Way Kandis watershed with area zoning highest form of residential areas in the amount of 1877.85 ha. (5) The highest pollution level in the class TSS Somewhat Polluted covering an area of 2635.85 hectares or 57.25% of the total upstream Way Kandis watershed with area zoning highest form of residential areas in the amount of 2148.06 hectares, (6) No TDS contamination occurred across the study area upstream Way Kandis watershed because of all extents of land cover (4603.76 ha) included in the category Not contaminated, (7) the level of Turbidity pollution occurs only in the category of pollution class Not contaminated covering an area of 3348.15 ha or 61.54% of the total upstream Way Kandis watershed with area zoning highest form of residential areas in the amount of 2398.45 H and Somewhat Polluted covering an area of 1255.61 ha or 38.46% of the total upstream Way Kandis watershed The highest area of zoning in the form of a residential area in the amount of 887.26 Ha. Keywords: identification, pollution, water surface, upstream, Way Kandis watershedGenerally, pollution in the waters is indicated with the presence of oxygen in the water or dissolved oxygen condition. To determine status of oxygen in the water as water pollution level  necessary to measure the COD (Chemical Oxygen Demand), TSS (Total Suspended Solid), TDS (Total Dissolve Solid) and turbidity (turbidity) as parameters of river water pollution. The purpose of this study is (1) to analyze the water quality of the sub watershed upstream Way Kandis, (2) make a map of the level of contamination of surface water in Sub Watershed (DAS) upstream Way Kandis. Stages of research include (i) gathering information and data, (ii) analysis of land use in sub watershed upstream Way Kandis, (iii) the analysis of water quality of upstream Way Kandis (iv) making maps contamination levels upstream Way Kandis, (v) the analysis of the level of River pollution Way Kandis. The results of this research, namely: (1) upstream Way Kandis watershed covering an area of 4603.76 hectares which includes the city of Bandar Lampung Territory and South Lampung regency and spread over four districts, namely Kemiling, Rajabasa, Natar and Jatiagung, (2) Usage land upstream Kandis Way watershed includes residential area of 3285.71 ha (71.37%), plantations covering an area of 429.52 ha (9.33%), a mixture of agricultural land area of 627.19 ha (13.62%), and poor land identified as the source map cloud-covered area of 118.98 ha (2.59%), (3) The level of water pollution in the upstream Way Kandis watershed divided into five zones, namely zones not polluted, slightly polluted zone, the critical zone polluted, heavily polluted and heavily polluted, (4) the highest COD pollution level in the class Very polluted covering an area of 2250.98 hectares or 48.79% of the total upstream Way Kandis watershed with area zoning highest form of residential areas in the amount of 1877.85 ha. (5) The highest pollution level in the class TSS Somewhat Polluted covering an area of 2635.85 hectares or 57.25% of the total upstream Way Kandis watershed with area zoning highest form of residential areas in the amount of 2148.06 hectares, (6) No TDS contamination occurred across the study area upstream Way Kandis watershed because of all extents of land cover (4603.76 ha) included in the category Not contaminated, (7) the level of Turbidity pollution occurs only in the category of pollution class Not contaminated covering an area of 3348.15 ha or 61.54% of the total upstream Way Kandis watershed with area zoning highest form of residential areas in the amount of 2398.45 H and Somewhat Polluted covering an area of 1255.61 ha or 38.46% of the total upstream Way Kandis watershed The highest area of zoning in the form of a residential area in the amount of 887.26 Ha. Keywords: identification, pollution, water surface, upstream, Way Kandis watershed